Effect of 5-fluorouracil on cellular response to proton beam in esophageal cancer cell lines according to the position of spread-out Bragg peak. (3rd April 2019) - Hojo, Hidehiro; Dohmae, Takeshi; Hotta, Kenji; Kageyama, Shun-Ichiro; Baba, Hiromi; Kohno, Ryosuke; Motegi, Atsushi; Tsuchihara, Katsuya; Akimoto, Tetsuo
Abstract: Introduction: To investigate enhancement by 5-fluorouracil (5-FU) of the sensitivity of cancer cells to proton beam irradiation and clarify the differences in the responses of the 5-FU-treated cells to proton beam irradiation according to the position of the cells on the spread-out Bragg peak (SOBP). Methods: OE21 human esophageal squamous cells were irradiated with a 235-MeV proton beam at four different positions on the SOBP. The effects of the irradiation plus 5-FU treatment on the cell survival were assessed by clonogenic assays and determination of the sensitizer enhancement ratio (SER). In addition, DNA double-strand breaks were estimated by measuring phospho-histone H2AX (γH2AX) foci formation in the cells at 0.5 and 24 h after irradiation. Results: The relative biological effectiveness (RBE) of proton beam irradiation against vehicle-control cells tended to increase with an increase in the depth of the cells on the SOBP. On the other hand, the degree of enhancement of the cellular sensitivity to proton beam irradiation by 5-FU was similar across all the positions on the SOBP. Furthermore, a marked increase in the number of residual γH2AX foci at 24 h post-irradiation was observed in the cells at the distal end of the SOBP. Conclusions: Our data indicated that the degree of enhancement by 5-FU of the sensitivity of OE21 cells to 235-MeV proton beam irradiation did not differ significantly depending on the position of the cells on the SOBP. Furthermore, the degree of increase in the number of γH2AX foci at 24 h after proton beam irradiation with or without 5-FU exposure did not differ significantly according to the position on the SOBP. The effect of 5-FU in enhancing the effect of proton beam irradiation on cancer cells may be constant for all positions on the SOBP.